Inclusive space for children in vertical housing - Pandelaki, Edward Endrianto; Firmandhani, Satriya Wahyu (Journal of Architecture and Urbanism, 2022)
This paper aims to explore forms and types of space in vertical housing in order to support the creation of inclusive living environments for children, through observing children’s activities and the available spaces and facilities. The field observation was carried out in vertical housing and their surrounding environments in Indonesia and Japan. Housing is currently in high demand in Indonesia, but land availability in cities is limited whereas children population in Indonesia has reached about one third of total population. Vertical buildings, thus, become one of feasible solution. Meanwhile Japan, as a developed country, has implemented vertical housing for a long time to meet society’s needs in various places and forms. Housing as a living environment which is suitable for children sometimes receives little attention, especially when there are challenges of limited resources. Therefore there are not many spaces that designated to accommodate various children activities. On the other hand, spaces in vertical housing have their potential to support a child-inclusive living environments. In this study, the qualitative method was employed to explore vertical housing living environments and spaces for children. The results indicated there are three scales of spaces that need to receive attention to the creation of inclusive living environment for children in vertical housing, namely micro, meso, and macro spaces.